Analysis and performance assessment of NH3 and H2 fed SOFC with proton-conducting electrolyte - Kalinci, Yildiz; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
The present paper investigates the performance of a solid oxide fuel cell based on proton conducting electrolyte (SOFC-H+) using one-dimensional steady-state model. The analysis covers a detailed electro-chemical model for H-2 and NH3 fuels. The direct internal reforming of NH3 is examined, and the effects of some operating parameters (e.g. temperature, pressure, fuel utilization and oxidant utilization) on the reversible cell potential are investigated. In addition, the overpotentials (including activation, ohmic and concentration) are calculated to study the irreversible behavior of the SOFC-H+ with some actual data operating conditions and material properties taken from the literature. In addition, effects of some operation and structural parameters on cell performance were examined. The present results indicate that the activation and the ohmic losses are considerable. The concentration overpotential at the anode side is negligible due to the fact that H2O is produced at the cathode side. The maximum power density is calculated as 3212 and 3113 W/m(2) at 1073 K and 1 atm for the fuels of H-2 and NH3. The results further show that H-2 provides better performance than NH3 at the same partial pressure. Moreover, NH3 is an excellent hydrogen carrier which is a potential candidate for SOFC-H+ due to its high hydrogen content and considerable cell performance. (c) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Solid oxide fuel cell; Proton conducting electrolyte; Ammonia; Hydrogen; Electrochemical performance; OXIDE FUEL-CELL; THERMODYNAMIC ANALYSIS; ANODE; CATHODE; HEAT; NI; Chemistry; Electrochemistry; Energy & Fuels